2016
DOI: 10.1088/1751-8113/49/49/495304
|View full text |Cite
|
Sign up to set email alerts
|

Analytical comparison of the first- and second-order resonances for implementation of the dynamical Casimir effect in nonstationary circuit QED

Abstract: We investigate analytically and numerically the nonstationary circuit QED setup in which N independent qubits interact with a single mode of the Electromagnetic field confined in a resonator. We consider the harmonic time modulation of some parameter (atomic transition frequency or the atom-field coupling strength) and derive the unitary dynamics up to the second order in the modulation depth for N = 1 and N 1. It is shown that all the resonant phenomena that occur for modulation frequencies ∼ 2ω0 (where ω0 is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 64 publications
0
12
0
Order By: Relevance
“…is the k-th modulation amplitude. It is worth noting that this particular choice for the modulation does not restrict the generality of our results, since for the regime considered here (g ω, Ω) a weak modulation of any system parameter produces similar results [21,37,85]. We suppose that the modulation frequency η (k) (t) may also slowly change as function of time.…”
Section: A Atom-field Interactionmentioning
confidence: 93%
See 1 more Smart Citation
“…is the k-th modulation amplitude. It is worth noting that this particular choice for the modulation does not restrict the generality of our results, since for the regime considered here (g ω, Ω) a weak modulation of any system parameter produces similar results [21,37,85]. We suppose that the modulation frequency η (k) (t) may also slowly change as function of time.…”
Section: A Atom-field Interactionmentioning
confidence: 93%
“…However, in Refs. [37][38][39]85] the authors showed that the number of excitations can be reduced instead, in what they called ADCE. This effect consists of coherent annihilation of two system excitations due to the approximate transition |g, n ←→ |e, n − 3 (for n ≥ 3), and takes place for the modulation frequency η ADCE ≈ 3ω − Ω 0 .…”
Section: A Atom-field Interactionmentioning
confidence: 99%
“…The results of that experiments stimulated many theoretical papers, suggesting further improvements of the experimental schemes [324][325][326][327][328][329][330][331][332][333][334][335][336][337]. The circuit QED with "artificial atoms" (qubits) was the subject of studies [338][339][340][341][342][343][344][345][346][347][348][349][350]. The most recent review on parametric effects in circuit QED can be found in [351].…”
Section: Circuit Dcementioning
confidence: 95%
“…The resulting dynamics resembles the well known phenomenon of parametric amplification [5], namely, photon pairs are generated from vacuum for the harmonic perturbation ω(t) = ν + ε sin(ηt), where ν is the unperturbed cavity frequency, ε is the amplitude and η = 2ν is the frequency of modulation [2]. Photon pairs can also be generated for fractional frequencies 2ν/k due to higher harmonics (for nonmonochromatic modulation [13]) or k-th order effects (for harmonic perturbation [14]), where k is a positive integer. Moreover, when the cavity field is coherently coupled to other quantum subsystems (e. g., multilevels atom or harmonic oscillators [15][16][17]) photons can be generated (or annihilated [18,19]) for several other modulation frequencies at the cost of entangling the subsystems.…”
Section: Introductionmentioning
confidence: 99%